USING PICTURE- ASSISTED LEXICAL INPUT APPROACH TO TEACH VOCABULARY TO THE POST-LINGUAL DEAF STUDENTS - Soe'oed, Rahmat; Ping, Maria Teodora; Thamrin, Abdul Rais (LLT Journal: A Journal on Language and Language Teaching, 2020)
English has been one of the compulsory subjects for special schools in Indonesia. However, there have been a rather limited number of studies conducted regarding the teaching of English under the framework of Special Education. Responding to this gap, this current study aimed at investigating whether a particular language teaching approach called Lexical Input Approach assisted by series of pictures could provide a desirable effect on post-lingual deaf students vocabulary mastery. This research employed a pre-experimental Single Subject with a multiple base (A-B-A-B) design. The sample included three 8th grade Junior High School students with the similarity of ages and hearing-loss history. The primary data in this study were taken by using assessments and analyzed statistically by calculating the Percentage of Data Points Exceeding the Median (PEM). The findings indicated that there was an improvement in the students vocabulary scores after the treatments (from 41/ novice advanced category to 46 and 51/ novice high category). Thus, it could be concluded that using Picture-Assisted Lexical Input Approach was effective to improve English vocabulary mastery for post-lingual deaf students.